The importance of living botanical collections for plant biology and the “next generation” of evo-devo research - Groover, Andrew; Dosmann, Michael (Frontiers in Plant Science, 2012)
Living botanical collections include germplasm repositories, long-term experimental plantings, and botanical gardens. We present here a series of vignettes to illustrate the central role that living collections have played in plant biology research, including evo-devo research. Looking towards the future, living collections will become increasingly important in support of future evo-devo research. The driving force behind this trend is nucleic acid sequencing technologies, which are rapidly becoming more powerful and cost-effective, and which can be applied to virtually any species. This allows for more extensive sampling, including non-model organisms with unique biological features and plants from diverse phylogenetic positions. Importantly, a major challenge for sequencing-based evo-devo research is to identify, access, and propagate appropriate plant materials. We use a vignette of the ongoing One Thousand Transcriptomes project as an example of the challenges faced by such projects. We conclude by identifying some of the pinch-points likely to be encountered by future evo-devo researchers, and how living collections can help address them.